The Clinical Benefits of Adding a Third Dimension to Assess the Left Ventricle with Echocardiography - Badano, Luigi P. (Hindawi Publishing Corporation, 2014)
Three-dimensional echocardiography is a novel imaging technique based on acquisition and display of volumetric data sets in the beating heart. This permits a comprehensive evaluation of left ventricular (LV) anatomy and function from a single acquisition and expands the diagnostic possibilities of noninvasive cardiology. It provides the possibility of quantitating geometry and function of LV without preestablished assumptions regarding cardiac chamber shape and allows an echocardiographic assessment of the LV that is less operator-dependent and therefore more reproducible. Further developments and improvements for widespread routine applications include higher spatial and temporal resolution to improve image quality, faster acquisition, processing and reconstruction, and fully automated quantitative analysis. At present, three-dimensional echocardiography complements routine 2DE in clinical practice, overcoming some of its limitations and offering additional valuable information that has led to recommending its use for routine assessment of the LV of patients in whom information about LV size and function is critical for their clinical management.